Effect of post-deposition annealing on the interface electronic structures of Al2O3-Capped GaN and GaN/AlGaN/GaN heterostructure - Duan, Tian Li (2019)
The interface electronic structures of GaN and GaN/AlGaN/GaN samples, capped with atomic-layer-deposited Al2O3 and subjected to varying post-deposition annealing (PDA) temperatures, are investigated by X-ray photoelectron spectroscopy (XPS) and Hall-effect measurement. XPS study shows a decrease in the Ga 3d and N 1s core level binding energy after a high-temperature PDA, implying a decrease of the interface defect density and the associated positive trapped-charge. From Hall-effect measurement, the density and mobility of the two-dimensional electron gas (2DEG) are found to decrease and increase, respectively, after PDA, supporting the XPS results. The XPS data, however, reveal a clear Ga-O signal for all samples and no apparent change in the Ga-O to Ga-N bond ratio for the range of annealing temperatures studied. These findings imply that the observed improvement in 2DEG mobility (and the associated decrease of interface defect density) should be ascribed to the structural change of the disordered GaOx interfacial layer formed during the atomic-layer-deposition of the Al2O3.